IMPLIKASI PENERAPAN CUSTOMER RELATIONSHIP MARKETING DAN DIGITAL MARKETING TERHADAP KEPUASAN KONSUMEN PADA PT GAPURA ANGKASA JOUMPA DENPASAR - NI PUTU MIRA DWI ASTUTI; I KOMANG MAHAYANA PUTRA; KASIANI KASIANI; COKORDA GEDE PUTRA A YUDISTIRA; I MADE WIDIANTARA (Universitas Mahasaraswati Mataram, 2020)
This study aims to determine the implications of Customer Relationship Marketing and Digital Marketing for consumer satisfaction at PT Gapura Angkasa JOUMPA Denpasar. The number of samples used was 68 people. The data used are primary data and secondary data with data collection techniques using a questionnaire. Data were analyzed descriptively quantitatively with SPSS 23.0 The results showed that partially 45.1% Customer Relationship Marketing (X1) had positive and significant implications for Consumer Satisfaction (Y) and 14% Digital Marketing (X2) had positive and significant implications for Consumer Satisfaction (Y). Simultaneously Customer Relationship Marketing (X1) and Digital Marketing (X2) have 59.1% implications for Consumer Satisfaction (Y) and 40.9% due to other factors outside the research model.